Taxonomy of Teaching Methods and Teaching Forms for Youth in Non-Formal Education in the National Youth Council of Slovenia - Vesna Miloševič Zupančič (Center for Educational Policy Studies Journal)
Research from the field of non-formal education (NFE) in youth work emphasises the central role of experiential learning and learning in groups. The present paper aims to research teaching methods and teaching forms in NFE in youth work. The research sought to answer the following research questions: ‘What teaching forms can be found in NFE for young people in youth councils on a national level in Slovenia?’ and ‘What teaching methods can be found in NFE for young people in youth councils on a national level in Slovenia?’ Data was collected using semi-structured interviews; the instrument was a list of questions. The empirical research was conducted in July 2016 with six interviewees. The results indicate that learning in selected NFE in the National Youth Council of Slovenia (MSS) is participatory, interactive, inclusive and student-focused; with central concepts of experiential learning and learning in groups. The key teaching form is learning in groups. However, individual work, work in pairs, programmed instruction and direct instruction are also present. The central and omnipresent teaching method is experiential learning. Problem-based learning, case-study method, action learning, and project-based learning are intertwined and connected to the experiential learning method. Other methods include verbal-textual methods, illustrative-demonstration methods, experimental methods, peer learning, and support methods. The conclusions are applicative in the didactic spectrum of NFE in youth work and in the wider didactic spectrum of adult learning. Implications for further research include teaching methods and forms in NFE inside the wider youth sector, internationally comparative and through quantitative research.